Field Mapping: What Is the "Media" of Media Studies?1. (September 2020) - Parks, Lisa
This short article explores the changing meanings of "media" in media studies in relation to emerging technologies and critical paradigms in the field. After brief discussion of various media studies approaches, including media ecologies and algorighmic cultures, the article discusses the institutional rise of data sciences and compares this field to media studies. The author argues that while the foundational assumptions, methodological frameworks, and mindsets of data sciences and media studies differ, curious co-existences can morph into lively collaborations rather than turf battles, and concludes by pointing to research that explemplies a productive synthesis.